2021
DOI: 10.1088/1742-6596/1892/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Study of Thermal Conductivity and Hardness Test of Carbon Black / Polymer Micro Composite

Abstract: In this research studied of Thermal Conductivity and Hardness Test of Carbon Black / Polymer Micro Composite at different weights ratios were studied. Five samples were prepared for Carbon black with epoxy resin, where the percentages of carbon black ranged between 2%, 4%, 6%, 8% and 10%. The mechanical properties of hardness test that the values of hardness for Carbon black decreasing with increased ratios of additive compared to the case of pure epoxy. For thermal conductivity coefficient (K), the results th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In contrast, conventional fillers (carbon black, metal nanoparticles, etc.) need to be filled at a rather higher percentage (e.g., >2 or even >10 wt%) to achieve results similar to those of 3DGF [ 32 , 33 , 34 ]. This advantage of 3DGF is due not only to the high thermal conductivity of CVD graphene itself, but also to the uniformly connected 3D graphene network that is very favorable for phonon and thermal transport.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, conventional fillers (carbon black, metal nanoparticles, etc.) need to be filled at a rather higher percentage (e.g., >2 or even >10 wt%) to achieve results similar to those of 3DGF [ 32 , 33 , 34 ]. This advantage of 3DGF is due not only to the high thermal conductivity of CVD graphene itself, but also to the uniformly connected 3D graphene network that is very favorable for phonon and thermal transport.…”
Section: Resultsmentioning
confidence: 99%
“…From the literature review, it has been concluded that epoxy as a matrix and carbon black as reinforcement is a less explored combination for thermal conductivity enhancement application. Carbon black has considerably higher thermal conductivity as compared to epoxy (Shahamatifard et al, 2021;Zweid et al, 2021). So it is expected to produce a better thermal conductive composite with epoxy resin.…”
Section: Pfrc As Thermal Conductormentioning
confidence: 99%